Implikasi Media Sosial (Instagram) pada Gaya Hidup di Kota Banjarmasin - Wahyuni, Nurul; Yohana, Ana; Hidayat, Rikzy Muslim (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2022)
This research was conducted using a descriptive study approach. This descriptive qualitative research aims to conduct an in-depth exploration of the role of social media (Instagram) and its implications for lifestyle in the city of Banjarmasin for FISIP students at Lambung Mangkurat University, Banjarmasin. This study used in-depth interviews with 20 informants, namely students of FISIP, Lambung Mangkurat University, Banjarmasin. The results of this study indicate that social media (Instagram) is very popular among young people, because it is considered more appropriate to their needs than other social media (such as Facebook which is considered more identical for older people). Social media (Instagram) has become an inseparable part of lifestyle in the scope of activities of daily life today. The position of social media (Instagram) in life can already be considered as a primary need because the intensity of access is > 10 hours per day. Through social media (Instagram), there is an externalization process (such as realizing dreams, channeling creativity, and the necessity to follow trends) and internalization processes (such as meeting the information needs of the outside world, the need for inspiration for innovation and creativity and a reference source for daily activities, e.g. choosing daily clothes) which is part of Social Construction Theory. Social Media (Instagram) which was originally functioned as a medium for exchanging information and interacting socially has also undergone many shifts, one of which has become a market place. The great potential of social media (Instagram) as a market place is recognized as being able to trigger entrepreneurial interest. All informants in this study are business actors (privately owned) although still on a small scale (monthly turnover <Rp 4,000,000, - per month) which are generally engaged in fashion, cosmetics and food. Running a business through social media is felt by the informants to add value to their lives (such as pride), because their lifestyle is not only focused on being consumers (shopping through Instagram social media) but also producers (earning additional money and the process of applying business knowledge gained from the learning process on campus). Keywords : Social Media, Instagram, Social Contruction Theory, Lifestyle